Gerardo Castillo Guzmán. Andean drunkenness: dramaturgical actions and breaking of hierarchies. Thesis presented to the Pontifical Catholic University for the title of Bachelor in Anthropology - Castillo, Gerardo (1996)
This review does not present a summary.